Meningkatan Hasil Belajar PAI Peserta Didik Dengan Menggunakan Model Pembelajaran PBL SDN 06 Makmur - Masniari, Masniari (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
The problem faced by students in learning is the low absorption capacity of learners. This is evident from the average learning outcomes of students, which remain concerning. The purpose of this research is to determine the learning outcomes of fifth-grade students in Islamic Religious Education (PAI) subjects after implementing the Problem-Based Learning (PBL) model. The method used is Classroom Action Research (CAR). The results of the study indicate that after the intervention, there was a significant improvement in student scores. The average score of fifth-grade students increased from 40% mastery to 60% after the intervention, with 11 students or 90% successfully mastering the subject matter.